Research status and prospect of grain refinement in aluminum alloy - Xinyue Zhang; Qichi Le; Dazhi Zhao; Yanchao Jiang; Yubo Wang; Tong Wang; Qiyu Liao (Journal of Materials Research and Technology)
Aluminum (Al) alloy, as an important lightweight material, has unique advantages such as low density, high specific strength, excellent ductility and corrosion resistance. As a result, it has wide application prospects in aerospace, military industry, automotive and other fields. It is of paramount importance to control the grain size and grain distribution in order to achieve excellent overall performance in Al alloys. The chemical, physical and composite methods applicable to grain refinement of Al alloy are described in this article. The current research status of Al alloy grain refinement treatments is summarized, the advantages and disadvantages of different methods are pointed out, as well as the direction of future development is envisioned. Such a review will provide a reference basis for the design of future refinement processes of high-quality and high-performance Al alloys, which is of great significance for promoting the application and development of Al alloys in high-end technological fields.